Photochemical synthesis of phosphinolines from phosphonium-iodonium ylides - Matveeva, Elena D.; Podrugina, Tatyana A.; Taranova, Marina A.; Borisenko, Anatolyi A.; Mironov, Andrey V.; Gleiter, Rolf; Zefirov, Nikolay S. (The journal of organic chemistry, 2011)
We describe three different series of experiments which were undertaken to test our hypothesis that during irradiation of phosphonium−iodonium ylides (1a, 1b) an electrophilic carbene is generated. By opposing the assumed intermediate to monosubstituted alkynes, we observed in the case of electron-rich substituents at the triple bond a domination of a 1,3-dipolar cycloaddition of the intermediate with the triple bond to yield furans. In the case of electron poorer substituents, the formation of phosphinolines prevails. A second series of experiments was carried out with mixed ylides in which one phenyl ring at the triarylphosphonium group was replaced by a thienyl group. In this case, we observe only an intramolecular reaction with the thienyl ring to yield the phosphinolines 21−23. In a third test, we replaced in the mixed ylides 1a, 1b the COR group by a CN substituent. This modification leads to phosphinolines only and avoids a 1,3-dipolar cycloaddition.
Published online: 22 December 2010
Gesehen am 12.08.2022